Psychological and Phenomenological Perspectives on the Hard Problem of Consciousness - Simard, Jonathan (University of Waterloo, 2017)
In reexamining the hard problem of consciousness through the history of the concept of mind, I argue that psychologists, cognitive scientists, and analytic philosophers of mind should return to the first-person perspective or “what it is like”, to uncover its existential-phenomenological structure. Classical phenomenology which describes the structure of first-personal consciousness provides insight into the intrinsic quality of conscious experience. However, this insight into experience as a phenomenon for the subject is problematic for psychological explanation. Phenomenal “qualia” are seen as extra-mental entities not necessary for explaining the nature of consciousness. There appears to be nothing left to explain about consciousness after considering evolutionary and computational paradigms in psychology. On this view, mind is thoroughly and completely a system of complex causal mechanisms. In response, I examine criticism of Husserl’s phenomenology that resulted from increasing skepticism of introspective methods throughout the history of psychology. Namely, that phenomenological analysis must equate to a Cartesian, solipsistic, and ultimately limited analysis. Heidegger’s existential-phenomenological interpretation of consciousness addresses concerns about introspective methods. I show that Heidegger’s examination of the self-representing nature of consciousness serves to destructure the mechanistic attitude we have developed toward mind. In doing so, one may provide an answer to the hard problem – “what it is like” to be a conscious human being - eluded by mechanistic explanations. While Heidegger’s account is only one possible interpretation of the human experience, the mechanistic understanding can then also be seen as only one interpretation among many of what properly explains human conscious experience.
Keywords: philosophy of mind; hard problem of consciousness; philosophical psychology; phenomenology; existentialism; heidegger; husserl; chalmers; qualia; mind and body